POJOK PENGINYONGAN PERPUSTAKAAN UIN PROF. K.H SAIFUDDIN ZUHRI PURWOKERTO SEBAGAI SARANA PELESTARIAN BUDAYA LOKAL BANYUMAS - Rheza Ega Winastwan; Annisa Nur Fatwa (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2022)
UIN Prof. K.H. Saifuddin Zuhri Library has a uniqueness, namely the availability of Pojok Penginyongan which provides various collections of local Banyumas culture. This can be said to be unique because it is still rare for university libraries to provide such services. This study aims to determine the purpose of the implementation, the obstacles faced in the technical aspects of collection management, both in terms of procurement, maintenance, and to service the collection. This research is a descriptive qualitative research. Research data collection are interviews, observations, and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. Based on the research findings, it can be seen that the purpose of the Pojok Penginyongan is to realize the Rector's work program to preserve local culture in the Banyumas residency. In relation to the number of collections, the library continues to develop or add to it by collaborating with public libraries and other university libraries and Banyumas community figure. For collection maintenance, the library applies the same mechanism as other collections, for example routinely fumigating, maintaining room temperature, and there are special guidelines for library users to minimize errors in the utilization of the Pojok Penginyongan collection.